Improving the Cost Estimation Method for Residential Building Projects in Syria During the Design Phase by Using Building Information Modeling - الجندي, جنى; عمران, جمال (Latakia University Journal -Engineering Sciences Series, 2022)
The process of cost estimation is one of the most important functions of the project and its efficiency is an essential part of its success, and with the development of the construction industry and the expansion of projects, the errors resulting from estimation by traditional methods have become large, and with the increase in competition between engineering companies, the time factor has become more important to complete the required project and play an effective role in achieving its objectives (time, cost and quality ) and thus his success. Obtaining accurate estimated costs requires accurate quantities of building elements, so the researcher evaluated the methods of calculating quantities by comparing the traditional methods based on two-dimensional diagrams and the smart methods based on models of building information modeling systems. The comparison was made using two quantitative calculating software for four building projects. Residential in Lattakia Governorate, which are the Excel program, and the Revit program that the researcher used, which is classified among the most important building information modeling software. Construction in the design phase contributes to high flexibility and speed in the accuracy of calculating the quantities of engineering project work and thus accuracy in calculating the project cost, and reaching the best quality of design documents to reduce as much design errors as possible that affect the cost of projects by designing an additional tool within the Revit program to obtain a model Accurate, error-free.